Desain Kemitraan Lingkungan Sekolah sebagai Upaya Penguatan Pendidikan Karakter Siswa Di Sekolah Menengah Atas Negeri 8 Kota Bandung - Gerry Catur Canova; Aribowo Aribowo; Pribowo Pribowo (Indonesian Journal of Social Work, 2024)
This research aims to develop a School Environmental Partnership Design as an effort to Strengthen Student Character Education at Bandung 8 State High School. The implementation of this research is in accordance with Presidential Regulation (Perpres) Number 87 of 2017 concerning Strengthening Character Education, which explains that character education is one of the issues that must always be implemented in schools, the main value in strengthening character must be reflected in the behavior of the school community through collaboration between various parties within the education unit. The tri-center educational partnership is a collaboration between educational units, families and the wider community that is based on the principles of mutual cooperation, mutual trust and a willingness to make sacrifices in building an educational ecosystem that fosters character and a culture of student achievement. The approach used in this study is a qualitative research method. The research design used is Participatory Action Research (PAR). Data collected from this research was conducted through data collection techniques such as observation, interviews and documentation studies. The primary data source in this study consisted of 6 informants who were selected according to the considerations required in the research. Based on the results of the initial assessment, the implementation of the ongoing partnership program at SMAN 8 Bandung is still less efficient in terms of management. Therefore, it is necessary to develop the process of implementing Partnership Design so that it is more efficiently adapted to field needs. After going through the implementation phase, it shows that the School Environmental Partnership Design that has been developed is considered to be able to increase mutual understanding and active participation from all educational units. This was marked by the results of the final reflection which showed enthusiasm from all informants in understanding this School Environmental Partnership Design. Technological development through the process of organizing, increasing capacity and participation can have a positive impact and become a reference in making the implementation of School Environmental Partnership Design more efficient.